Outcomes of Patients Who Have Undergone AV Shunt Procedure at Dr. Zainoel Abidin General Hospital in Banda Aceh - Khalikul Razi; Yopie Afriandi Habibie; Zulfan Zulfan; Rovy Pratama (Budapest International Research and Critics University, 2021)
In recent decades, kidney disease has been documented as a global public health problem. The current challenge is about improving the treatment of chronic kidney disease (CKD) patients in order to provide a longer life expectancy for them. In hemodialysis, there has been a considerable development in finding access to the vascular system, one of which developments was the creation of arteriovenous access by Cimino and Brescia (called an AV shunt). Research on the AV shunt is still limited, so the researchers are interested in conducting this descriptive epidemiological survey study on the profile of patients undergoing AV shunt procedures at Dr. Zainoel Abidin General Hospital in Banda Aceh in 2017. Data were obtained retrospectively from the medical records of the Central Surgery Installation Department of Dr.Zainoel Abidin General Hospital in Banda Aceh, and there were 105 patients have undergone AV shunt, 72 men (68.6%) and 33 women (31.4%). The frequency based on the age was the risking age about 45-54 years as many as 30 people (28.6%). Based on the outcomes obtained 95 people (90.48%) who have used the AV shunt for hemodialysis access, consisting of 66 men (62.86%) and 29 women (27.62). Based on the duration of use, AV Shunt is mostly used for 1 year with the number of 48 patients (50.52%) in the proportion of men and women were 38.95% and 11.57%. With an average duration of use of AV Shunt 2,6 years. From the results of this study, we conclude that the result was obtained that the highest cases in patients who have undergone AV Shunt is man as much as 68.6%. Furthermore, Pertaining to this study, it was obtained that the majority of age who undergo Av shunt is 45-54 years. In addition, the result of this study showed that the success rate of surgery AV shunt in Dr. Zainoel Abidin General Hospital in Banda Aceh was high. It is about 90, 48% with an average duration use of Av shunt is 2.6 years.